National Agri-food Labeling and Improvement of Consumers’ Utilization (영문판) - 김상효 (농식품 표시정보 현황 및 활용도 제고방안, 2019)
When consumers choose an agri-food product, it is inevitable to have information gaps between producers or distributors and consumers. Such asymmetrical information causes adverse choices and moral hazards, leading to market failure. Food labeling and certification programs are typical policies to ameliorate market failure, resulted from asymmetrical information. However, consumer utilization of food labeling and certification programs remain at a low level. Korea is not the only country facing this problem. Prior studies agreed that consumer utilization of agri-food labels remains low and improvement is needed, however, they only emphasized educations and did not suggest other specific alternatives. Also, previous studies were mainly carried out by focusing on the role of information suppliers. Our study, therefore, focuses on consumer’s perspectives toward label information. This study describes all aspects of agri-food labeling and certification programs, and then, reviews consumer utilization based on food type if required. The purpose is to establish specific and practical strategies for encouraging consumers to use agri-food label information through the applications of behavioral economics, field analysis, and online experiments.